Sagot :
answer:
( x , y ) = ( 3 , 1 )
2x + y = 7
5x - y = 14
solve the equation for y
y = 7 - 2x
5x - y = 14
substitute the given value of y into the equation 5x - y = 14
5x - ( 7 - 2x ) = 14
solve the equation for x
x = 3
substitute the given value of x into the equation y = 7 - 2x
y = 7 - 2 x 3
solve the equation for y
y = 1
the possible solution of the system is the ordered pair ( x , y )
( x - y ) = ( 3 , 1 )
checked if the ordered pair is the solution of the system of equations
2 x 3 + 1 = 7
5 x 3 - 1 = 14
simplify the equalities
7 = 7
14 = 14
since all of the equalities are true, the ordered pair is the solution of the system
( x , y ) = ( 3 , 1 )